The Effects of Cr/Mo Micro-Alloying on the Corrosion Behavior of Carbon Steel in CO2-Saturated (Sweet) Brine under Hydrodynamic Control. Issue 5 (1st January 2018) - Sk, M. Hassan; Abdullah, A. M.; Qi, J.; Ko, M.; Ingham, B.; Laycock, N.; Ryan, M. P.; Williams, D. E.
Abstract : The effects of micro-alloying of plain carbon steel with Cr and Mo on the corrosion behavior in CO2 -saturated (sweet) brine (0.5 M NaCl, pH 6.6) environment, under hydrodynamic conditions, at 80°C were investigated. Crystalline siderite/chukanovite scales formed on all the alloys. Analysis of potentiostatic current transient data suggest that there exists a synergistic interaction between Cr and Mo, which induces more rapid crystallization of the scale compared to Mo-free steels. Increasing the Mo content also suppressed the transport-dependent dissolution current passing through the initially-present amorphous surface film. TEM images of the FIB-sectioned corrosion scales confirm that the corrosion scale formed on 1Cr0.7Mo is comparatively thinner and yet offers greater protectiveness when compared to the plain carbon steel.